2002
DOI: 10.1073/pnas.122153699
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics of Salmonella : Gene acquisitions revealed by microarray analysis

Abstract: The presence of homologues of Salmonella enterica sv. Typhimurium LT2 genes was assessed in 22 other Salmonella including members of all seven subspecies and Salmonella bongori. Genomes were hybridized to a microarray of over 97% of the 4,596 annotated ORFs in the LT2 genome. A phylogenetic tree based on homologue content, relative to LT2, was largely concordant with previous studies using sequence information from several loci. Based on the topology of this tree, homologues of genes in LT2 acquired by various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
210
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(231 citation statements)
references
References 35 publications
18
210
1
2
Order By: Relevance
“…arizonae (group IIIa) and S. bongori (group V) isolates. This is consistent with previous DNA microarray studies (14,45). However, only S. enterica subsp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…arizonae (group IIIa) and S. bongori (group V) isolates. This is consistent with previous DNA microarray studies (14,45). However, only S. enterica subsp.…”
Section: Discussionsupporting
confidence: 93%
“…For pathogenic Salmonella spp., genome sequencing efforts have identified over 15 distinct fimbrial types (Salmonella enterica serovars Typhimurium [42], Typhi [44], and Paratyphi [41]). Pioneering work by Baumler et al (5) and subsequent genomic comparisons (14,45,61) revealed that most fimbrial operons have a scattered distribution throughout the salmonellae. Early hypotheses that fimbriae were involved in adherence to host cells suggested that numerous fimbrial types would contribute to the host specificities and tissue tropisms of different Salmonella spp.…”
mentioning
confidence: 99%
“…In an analysis of Salmonella genomes by microarray techniques using the genome of serotype Typhimurium LT2 as a standard, approximately 90% of the annotated LT2 open reading frames (ORFs) were homologous among members of all seven subgroups (112). Comparative genomic analysis of serotypes Typhimurium and Typhi (full genome sequences), and serotypes Dublin, Enteritidis, and Paratyphi (draft sequences) revealed that in each genome approximately 10 to 12% of unique DNA was acquired by horizontal gene transfer (96,109).…”
Section: Bacterial Geneticsmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) is a powerful genetic tool for the study of bacteria (Dobrindt et al, 2003;Fitzgerald et al, 2001Fitzgerald et al, , 2003Fukiya et al, 2004;Israel et al, 2001;Leavis et al, 2007;Lindsay et al, 2006;Paauw et al, 2008;Porwollik et al, 2002;Salama et al, 2000). Most CGH arrays have been designed from annotated wholegenome sequences.…”
Section: Introductionmentioning
confidence: 99%